CURRENT STATUS AND FUTURE STRATEGIES IN THE EPIDEMIOLOGY OF LEPTOSPIROSIS IN THE CANTON OF PORTOVIEJO, PROVINCE OF MANABÍ, ECUADOR - Lazo, Leonel (2017)
The objective of the present work was to perform a descriptive observational analysis of the current status and occurrence of cases of leptospirosis in the population of the canton of Portoviejo in the province of Manabí, Ecuador. In addition, the approach of future strategies that will be carried out to improve the prevention and control of the disease in animals and humans was developed. The incidence of cases of leptospirosis was determined by epidemiological weeks and years, in a time series that covered the 2014-2017 period. An analysis of the occurrence of cases was carried out, with the aim of describing the characteristics of their tendency, seasonality and the channel of habitual behavior. It is concluded that in the province of Manabí the incidence of leptospirosis in the human population is relatively low taking into account the number of inhabitants per canton. The highest number of outbreaks was recorded during 2014 and the increase in the number of cases is evident in the last period of 2017. The age group with the highest number of cases is 20 to 49 years old, with a predominance of females, during 2015. Leptospirosis manifests a seasonal behavior with greater occurrence in the months of February, March, April and June. The endemic pathway of the occurrence of leptospirosis in the studied territory is from one to six monthly cases; evidencing an increase in the occurrence during 2017 with several months in the alert zone.